2012
DOI: 10.1136/tobaccocontrol-2011-050391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco control policy on quitting and nicotine dependence among women in five European countries

Abstract: Objective Describe differences in and factors associated with former smoking and nicotine dependence among women in Ireland, Sweden, France, Italy and the Czech Republic. Methods A cross-sectional, random digit dial telephone survey of 5000 women, ages 18 and older, conducted in 2008. Analyses were conducted using logistic regression models. Results Respondents from Ireland and Sweden had statistically significantly higher odds of having quit smoking within the 5 years prior to survey administration as com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The quit ratio of 55.2 (57.1 male and 53.2 female) in our study was remarkably higher than those in former Soviet Union (fSU) and Baltic countries and more consistent with estimates from two comparative European studies that were inclusive of East European countries [ 4 , 27 ]. Our estimates were closer to quit ratios in southern Europe and yet lower than in countries in the north, as in the study by Shaap et al In the latter, the quit ratios in the Czech sample (2002) were slightly lower than our estimates while the magnitude of association between education and quitting was consistent with our findings [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…The quit ratio of 55.2 (57.1 male and 53.2 female) in our study was remarkably higher than those in former Soviet Union (fSU) and Baltic countries and more consistent with estimates from two comparative European studies that were inclusive of East European countries [ 4 , 27 ]. Our estimates were closer to quit ratios in southern Europe and yet lower than in countries in the north, as in the study by Shaap et al In the latter, the quit ratios in the Czech sample (2002) were slightly lower than our estimates while the magnitude of association between education and quitting was consistent with our findings [ 4 ].…”
Section: Discussionsupporting
confidence: 90%
“…With the proportion highly dependent being much greater than those with low motivation, measures targeted specifically at high dependence groups may therefore be warranted with the aim of reducing dependency in the smoker population. A similar recommendation was made in a recent European study [35], that found that female smokers in countries with welldeveloped tobacco control policies, such as Ireland and Sweden, tended to have higher dependence than those in countries yet to establish these. Targeted measures could include harm reduction interventions such as the provision of pharmacotherapies for reduction as a first step towards quitting, or more targeted and tailored mass media campaigns for heavy smokers.…”
Section: Practical Implicationssupporting
confidence: 67%
“… 10 Due to the use of these different instruments, the reported prevalence of tobacco dependence in current smokers varies greatly, ranging from 22% to 69% across different studies. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 In China, no national data on tobacco dependence is available, with only several small epidemiological studies reporting the prevalence of this condition. 12 , 14 …”
Section: Introductionmentioning
confidence: 99%